INTEGRATING ISLAMIC VALUES INTO ELT MATERIALS FOR THE ELEVENTH GRADE STUDENTS OF MAHYAJATUL QURRA’ ISLAMIC BOARDING SCHOOL TAKALAR (International Conference on Social and Islamic Studies, 2022)
Teaching and learning materials as the one of the significant components in English language teaching should be appropriate with students’ characteristics, settings, and needs to help them learning meaningfully and reach the learning goals effectively. In Islamic boarding school (Pesantren), students’ life cannot be separated with Islamic values. Therefore, to help the students learning meaningfully based on their real-life context and needs, the integration of Islamic values into English teaching and learning materials is highly necessary. This research is intended to develop an English textbook integrated with Islamic values for the XI grade students of Mahyajatul Qurra’ Islamic Boarding School Takalar to present a more relevant learning materials to help the students learning meaningfully, achieving the learning goals effectively, and strengthening their Islamic characters. The researcher implemented RnD method with ADDIE model as the instructional design framework. In developing the materials, the researcher arranged the textbook integrated with Islamic values which are represented in Islamic names, pictures, verses of Qur’an and hadith, Islamic messages in dialogue, general-moral messages, and in the tasks/activities. This research may become a relevant literature resource for other researchers regarding the form of Islamic values integration into ELT materials. In addition, the developed textbook in the future is expected to assist the teachers in enhancing students’ motivation and to lead the students learning meaningfully as well as improving their Islamic characters that can be contribute to internalize in their daily life.